Creating a comfortable environment in public spaces using salutogenic and navigational design - Khomenko Olga V. (Архитектон, 2025)
The principles of salutogenic approach to the design of public spaces are considered, focusing on the benefits of salutogenic and navigation design in the creation of a comfortable environment that strengthens the physical, psychological and social wellbeing of an individual. Key factors that can be applied in this type of design to improve quality of life are indentified. Three components of the sense of coherence are considered as proposed by A. Antonovsky: comprehensibility, manageability, meaningfulness. A salutogenic approach to the development of navigation systems is suggested to allow designers to develop a navigation system model that would help find one’s way, but also produce a positive impact on the user. The system-homeostatic approach is used to demonstrate the stability of the navigation system. The indicators of urban environment comfort index are analyzed. In the conclusion, a list of components of a comfortable environment is provided.